2014
DOI: 10.1175/jtech-d-14-00027.1
|View full text |Cite
|
Sign up to set email alerts
|

High-Water Alerts from Coinciding High Astronomical Tide and High Mean Sea Level Anomaly in the Pacific Islands Region

Abstract: A technique to produce high-water alerts from coinciding high astronomical tide and high mean sea level anomaly is demonstrated for the Pacific Islands region. Low-lying coastal margins are vulnerable to episodic inundation that often coincides with times of higher-than-normal high tides. Prior knowledge of the dates of the highest tides can assist with efforts to minimize the impacts of increased exposure to inundation. It is shown that the climate-driven mean sea level anomaly is an important component of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…We found that extreme storm-tide elevations are strongly correlated with MHWS elevation. This affirms current practice in NZ of forecasting "red-alert" tide dates when high-tide peaks are predicted to be unusually high (Bell, 2010;Stephens et al, 2014) (see NZ Storm-Tide Red-Alert Days; National Institute of Water and Atmospheric Research; https://niwa.co.nz/ our-science/coasts/tools-and-resources/tide-resources, last access: 10 March 2020). The red-alert tide concept works in New Zealand because the semi-diurnal tides dominate sea-level variability and storm surges are limited to mostly < 0.5 m, which is approximately 25 % of the average tidal range (Stephens et al, 2014).…”
Section: Tidal Influencesupporting
confidence: 72%
See 3 more Smart Citations
“…We found that extreme storm-tide elevations are strongly correlated with MHWS elevation. This affirms current practice in NZ of forecasting "red-alert" tide dates when high-tide peaks are predicted to be unusually high (Bell, 2010;Stephens et al, 2014) (see NZ Storm-Tide Red-Alert Days; National Institute of Water and Atmospheric Research; https://niwa.co.nz/ our-science/coasts/tools-and-resources/tide-resources, last access: 10 March 2020). The red-alert tide concept works in New Zealand because the semi-diurnal tides dominate sea-level variability and storm surges are limited to mostly < 0.5 m, which is approximately 25 % of the average tidal range (Stephens et al, 2014).…”
Section: Tidal Influencesupporting
confidence: 72%
“…This affirms current practice in NZ of forecasting "red-alert" tide dates when high-tide peaks are predicted to be unusually high (Bell, 2010;Stephens et al, 2014) (see NZ Storm-Tide Red-Alert Days; National Institute of Water and Atmospheric Research; https://niwa.co.nz/ our-science/coasts/tools-and-resources/tide-resources, last access: 10 March 2020). The red-alert tide concept works in New Zealand because the semi-diurnal tides dominate sea-level variability and storm surges are limited to mostly < 0.5 m, which is approximately 25 % of the average tidal range (Stephens et al, 2014). Coastal or hazard managers are advised to keep a close watch on the weather for lower barometric pressure and adverse winds during the red-alert tide days, as even a minor storm or swell event could lead to inundation of low-lying areas, especially if accompanied by waves (Bell, 2010).…”
Section: Tidal Influencesupporting
confidence: 72%
See 2 more Smart Citations
“…Daily tidal water level variations are a key control on shore ecology; access to marine environments via boat and shipping infrastructure such as ports, jetties and wharves; drainage links between the ocean and coastal hydrosystems such as lagoons and estuaries; and the duration and frequency of opportunities to access the intertidal zone for recreation and food harvesting purposes. Fortnightly and monthly tidal envelope variations, such as those associated with spring-neap and perigean-apogean cycles, have similar moderating roles on human usage of intertidal and shoreline environments, and additionally these medium term variations in tide levels are important factors in coastal inundation risks (Menéndez & Woodworth, 2010;Stephens 2015;Stephens et al, 2014;Wood, 1978Wood, , 1986). High perigean-spring tides, for example, interact with extreme weather events (including low pressures, strong winds and extreme rainfall) to produce significant coastal inundation in low-lying coastal settlements such as on deltas (Hart et al, 2015).…”
Section: Discussionmentioning
confidence: 99%